Hubungan Self Esteem dan Sosial Ekonomi Orangtua dengan Perilaku Asertif Siswa Di Sekolah UPT SMPN 1 Nibung Hangus Kabupaten Batubara - Dini Ramadhani; Nur' Aini; Abdul Munir (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
This study was aimed to see the correlation between self ssteem and economic Social of parents with assertive behavior of the UPT SMPN 1 Nibung Hangus students. The population in this research is the students of UPT SMPN 1 Nibung Hangus students amounting 250 students and the sample was 154 students where the sample was taken using proportional random sampling. Questionnaire were data collection techniques, data analysis is recorded with product moment correlation, the hypothesist test used, t test, F test, and determination test. The results showed that: (1) There was a significant positive correlation between self ssteem and economic social of parents with assertive behavior with the significance value of 0.001 < 0,05. The contribution of self esteem and economic social of parents is seen from the value of the coefficient of determination (R2) = 0,620 or 62,0%. (2) There was a significant positive correlation between self esteem with assertive behavior the significance value of 0.002 < 0,05. The contribution of self esteem is seen from the coefficient of determination (R2) = 54,4%. 3) There was a significant positive correlation between economic social of parents with assertive behavior with the significance value of 0,01<0,05. Contribution of economic status of parents seen from the value of the coefficient of determination (R2) = 0,620 or 62,0%. Thus, it can be concluded that there is a significant correlation between self ssteem and economic Social of parents with assertive behavior of the UPT SMPN 1 Nibung Hangus students.